Synthesis, characterization and antibacterial activity of Ag incorporated ZnO–graphene nanocomposites. Issue 91 (16th September 2016) - Naskar, Atanu; Bera, Susanta; Bhattacharya, Rahul; Saha, Pritam; Roy, Sib Sankar; Sen, Tuhinadri; Jana, Sunirmal
Abstract : One pot low temperature synthesis of silver incorporated ZnO–chemically converted graphene nanocomposites is reported. An optimum of 10% Ag incorporated sample at 6.25 μg ml −1 dose shows an excellent antibacterial activity on E. coli and S. aureus . Abstract : The present work reports on the successful one-pot surfactant-free in situ synthesis of silver incorporated ZnO–chemically converted graphene (CCG) nanocomposites (AZG) by adopting a low temperature solution technique from zinc acetate dihydrate, silver nitrate and graphene oxide, and the varying silver content (up to 20% Ag with respect to Zn) in the precursors. X-ray diffraction and transmission electron microscopy studies confirmed the presence of Ag and ZnO nanoparticles (NPs), distributed uniformly with CCG. FTIR, Raman, UV-visible and X-ray photoelectron spectroscopic analyses confirmed the existence of interaction between CCG with the inorganic moieties (ZnO/Zn 2+ and Ag NPs) of the AZG samples. In vitro cytotoxicity and quantitative cell viability of the human ovarian teratocarcinoma cell line (PA1) was studied up to a maximum sample concentration of 200 μg ml −1 . Antibacterial activity was also measured on E. coli and S. aureus to confirm the efficiency of the nanocomposite, especially for killing bacterial cells without any major effect on the surrounding cells. Among the nanocomposites, the 10% Ag incorporated sample at a 6.25 μg ml −1 dose showed excellent antibacterial activity with negligible cytotoxicity. This simple strategy could be applied in the synthesis of Ag incorporated different metal oxide–CCG nanohybrids for antibacterial applications.